2022
DOI: 10.21315/mjms2022.29.4.3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Effect of Saffron Extract on Lipid Profile in Hyperlipidaemic Experimental Animal Models

Abstract: Saffron is widely used in traditional medicine to treat various medical disorders, including hyperlipidaemia. This study aims to systematically review the effects of saffron extract (SE) on lipid profile in in vivo studies. A strategic literature search was done following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The Scopus, PubMed (MEDLINE) and Web of Science databases and hand-searching methods were utilised to identify studies published up to January 2020 that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The possible justification for these results is due to the therapeutic effect of saffron. Aligning with the present results, previous studies have demonstrated that saffron exhibits hypolipidemic effects [8,31,37,38].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…The possible justification for these results is due to the therapeutic effect of saffron. Aligning with the present results, previous studies have demonstrated that saffron exhibits hypolipidemic effects [8,31,37,38].…”
Section: Plos Onesupporting
confidence: 92%
“…Presently, saffron stigma extracts and its major bioactive compounds, crocin, crocetin, safranal, and picrocrocin are well-established to produce a variety of pharmacological and therapeutic effects on cardiovascular diseases [6][7][8], asthma [9,10], depression [11,12], dementia [13], premenstrual syndrome [14,15], obesity [16], and diabetes [17]. Although most studies were performed in animals, small-scale clinical trials have also been reported in recent years [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, clinical studies performed on patients with mild to moderate Alzheimer's disease showed significantly better outcomes on cognitive function after administering saffron capsules in comparison to placebo [17], while the same effectiveness was observed when saffron capsules were compared to donezepril [18]. Studies carried out on different animal models demonstrated the efficiency of saffron and its active ingredients, crocin and safranal, in the treatment of pathological conditions such as atherosclerosis [19,20], cancer [21][22][23], hyperglycemia, and glucose uptake/metabolization [24]. It is interesting to note that Shirali et al [25] reported the ability of crocin to significantly lower the formation of advanced glycation end-products, in addition to the levels of serum glucose, triglycerides, and total cholesterol in the diabetic rats.…”
Section: Introductionmentioning
confidence: 91%
“…I read with interest the manuscript titled ‘A systematic review on the effect of saffron extract on lipid profile in hyperlipidaemic experimental animal models’ by Abd Rahim et al ( 1 ). In fact, saffron possesses many medicinal properties because it contains a large number of bioactive compounds, especially carotenoids (crocin and crocetin) and terpenes ( 2 ).…”
mentioning
confidence: 99%
“…in daily meals. For medical and pharmaceutical purposes, some studies use ethanol, aqueous ethanol and water to isolate bioactive compounds from raw materials ( 1 ). We can also use methanol, ethyl acetate and other solvents to recover the chemical components.…”
mentioning
confidence: 99%